2016
DOI: 10.5194/amt-9-2253-2016
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving atmospheric turbulence information from regular commercial aircraft using Mode-S and ADS-B

Abstract: Abstract. Navigational information broadcast by commercial aircraft in the form of Mode-S EHS (Mode-S Enhanced Surveillance) and ADS-B (Automatic Dependent Surveillance-Broadcast) messages can be considered a new source of upper tropospheric and lower stratospheric turbulence estimates. A set of three processing methods is proposed and analysed using a quality record of turbulence encounters made by a research aircraft.The proposed methods are based on processing the vertical acceleration or the background win… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Indirect methods are based on the inertial-range arguments that follow from Kolmogorov's hypotheses (Kolmogorov 1941;Albertson et al 1997). Such methods are commonly used in the analysis of low-and moderate-resolution velocity time series of in situ airborne measurements (Sharman et al 2014;Kopeć et al 2016a). In the case of fully resolved velocity signals, the direct methods, based on measuring the mean variance of velocity fluctuation gradients, can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect methods are based on the inertial-range arguments that follow from Kolmogorov's hypotheses (Kolmogorov 1941;Albertson et al 1997). Such methods are commonly used in the analysis of low-and moderate-resolution velocity time series of in situ airborne measurements (Sharman et al 2014;Kopeć et al 2016a). In the case of fully resolved velocity signals, the direct methods, based on measuring the mean variance of velocity fluctuation gradients, can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Kopeć et al (2016) have shown that the dissipation rates estimated from such N L using very lowresolution signals, although underestimated, were proportional to calculated using structure functions scaling in the inertial range. In the follow up analyses we found that this is also the case for moderate-resolution airborne data from different sources.…”
Section: Introductionmentioning
confidence: 99%
“…Possible candidates for the real-time data are the navigational information of commercial aircraft such as the ADS-B and Mode-S EHS. Given that the set-up for the ADS-B or Mode-S EHS receiving stations does not require a lot of work or money for transmission of the data, EDR estimates from ADS-B and Mode-S EHS (e.g., Kopeć et al, 2016) could greatly support the construction of a turbulence database and statistics globally, together with on-board based (both fine and coarse) EDR measurements (e.g., Sharman et al, 2014;Gill, 2014) and other sources of data like radiosonde, weather radars, and lidars (e.g., Bodini et al, 2019;Ko et al, 2019;Kim et al, 2021aKim et al, , 2021b. We leave the real time experiment as a future study, because it requires a huge amount of additional works to set up the receivers, to conduct the real-time quality control, and so on (e.g., de Haan, 2011;Stone and Pearce, 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%